Influence of anxiety on health outcomes in COPD - Eisner, Mark D; Blanc, Paul D; Yelin, Edward H; Katz, Patricia P; Sanchez, Gabriela; Iribarren, Carlos; Omachi, Theodore A (Thorax, 2010)
BackgroundPsychological functioning is an important determinant of health outcomes in chronic lung disease. To better define the role of anxiety in chronic obstructive pulmonary disease (COPD), a study was conducted of the inter-relations between anxiety and COPD in a large cohort of subjects with COPD and a matched control group.MethodsData were used from the FLOW (Function, Living, Outcomes, and Work) cohort of patients with COPD (n=1202) and matched controls without COPD (n=302). Anxiety was measured using the Anxiety subscale of the Hospital Anxiety and Depression Scale.ResultsCOPD was associated with a greater risk of anxiety in multivariable analysis (OR 1.85; 95% CI 1.072 to 3.18). Among patients with COPD, anxiety was related to poorer health outcomes including worse submaximal exercise performance (less distance walked during the 6-min walk test: −66.3 feet for anxious vs non-anxious groups; 95% CI −127.3 to −5.36) and a greater risk of self-reported functional limitations (OR 2.41; 95% CI 1.71 to 3.41). Subjects with COPD with anxiety had a higher longitudinal risk of COPD exacerbation in Cox proportional hazards analysis after controlling for covariates (HR 1.39; 95% CI 1.007 to 1.90).ConclusionCOPD is associated with a higher risk of anxiety. Once anxiety develops among patients with COPD, it is related to poorer health outcomes. Further research is needed to determine whether systematic screening and treatment of anxiety in COPD will improve health outcomes and prevent functional decline and disability.